Weakening of Corticomuscular Signal Coupling During Voluntary Motor Action in Aging - Bayram, Mehmed Bugrahan; Siemionow, Vlodek; Yue, Guang H. (OXFORD UNIV PRESS INC, 2015)
Background. Aging is associated with muscle weakness and impairment in performing skilled motor tasks. Still, little is known about whether the link or functional coupling or connection between the central and peripheral systems during voluntary motor performance is compromised in the elderly subjects. The purposes of this study were to estimate functional corticomuscular connection (CMC) strength in the elderly subjects by calculating EEG-EMG coherence during voluntary motor performance, determine the relationship between the CMC and voluntary muscle force, and compare these between the old and the young subjects. Methods. Maximal voluntary contraction (MVC) of elbow flexion (EF) and EFs at three submaximal (20\%, 50\%, and 80\% MVC) levels were performed in 28 healthy older (74.96 +/- 1.32 years) and 20 young (22.60 +/- 0.90 years) individuals, while EEG and EMG from biceps brachii, brachioradialis, and triceps brachii muscles were recorded simultaneously. Results. Compared with the young, older individuals exhibited significantly weakened CMC at all force levels tested. There was a proportional relationship between the CMC and EF force and high-positive correlation between the CMC and EF strength in both groups. Conclusions. Weakened CMC in aging may be a major factor contributing to age- related muscle weakness, and the linear relationship between the CMC and voluntary muscle force suggests dependence of force output on translation of the descending command to muscle electrical signal.
Keywords: Brain aging; Motor control; Biomarkers